The Impact of Innovative Activities on Social Capital and Business Performance: A Study of Young Entrepreneurs in Malang City - Mu'ammal, Immanuel; Firmansyah, Muhammad; Hilmi, Luqman Dzul (Peradaban Journal of Economic and Business, 2025)
This study examines the influence of social capital on business performance and the mediating role of innovative activities, with a specific focus on young entrepreneurs in the Greater Malang area. Using a quantitative positivist approach, data were collected through questionnaires from 65 entrepreneurs aged 18–30 who had operated their businesses for more than two years. Structural Equation Modeling (SEM-PLS) with WarpPLS 8.0 was employed for analysis. The results indicate that social capital significantly affects both business performance (β = 0.255; p < 0.001) and innovative activities (β = 0.381; p < 0.001). Innovative activities, in turn, strongly influence business performance (β = 0.551; p < 0.001) and mediate the relationship between social capital and business performance (β = 0.340; p < 0.001). These findings extend the literature by demonstrating how social networks foster innovation as a pathway to performance enhancement in emerging economies. Practically, this research highlights the importance of integrating social capital and innovation into entrepreneurial development strategies, particularly for youth-led businesses. Penelitian ini mengkaji pengaruh modal sosial terhadap kinerja bisnis serta peran mediasi aktivitas inovatif, dengan fokus pada wirausahawan muda di wilayah Malang Raya. Dengan menggunakan pendekatan kuantitatif-positivistik, data dikumpulkan melalui kuesioner dari 65 wirausahawan berusia 18–30 tahun yang telah menjalankan usahanya lebih dari dua tahun. Analisis data dilakukan dengan Structural Equation Modeling (SEM-PLS) menggunakan WarpPLS 8.0. Hasil penelitian menunjukkan bahwa modal sosial berpengaruh signifikan terhadap kinerja bisnis (β = 0,255; p < 0,001) maupun terhadap aktivitas inovatif (β = 0,381; p < 0,001). Aktivitas inovatif, pada gilirannya, berpengaruh kuat terhadap kinerja bisnis (β = 0,551; p < 0,001) dan memediasi hubungan antara modal sosial dan kinerja bisnis (β = 0,340; p < 0,001). Temuan ini memperluas literatur dengan menunjukkan bagaimana jejaring sosial mendorong inovasi sebagai jalur peningkatan kinerja dalam konteks ekonomi berkembang. Secara praktis, penelitian ini menekankan pentingnya integrasi modal sosial dan inovasi dalam strategi pengembangan kewirausahaan, khususnya bagi usaha yang dipimpin generasi muda.